PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN MODEL DISCOVERY LEARNING PADA MATERI LINGKARAN UNTUK SISWA KELAS XI - Ifty Wasilah; Atma Murni; Jalinus Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research is by the limited availability of mathematic learning instruments as supporting learning referring to Curriculum 2013. This research purpose is produce to mathematics learning instrument (Syllabus, Lesson Plan and Student Worksheet) which refers to Discovery Learning model on subject Circle for SMA/MA with minimum valid and practical criteria. This reserch method used is 4D model by Thiangrajan, that consist of define, design, development and dissemination, but the reserch only done to development step due to time constraints. In this research, a limited trial was conducted on 13 students of grade XII. Based on the results data analysis, it can be concluded that mathematics learning is very valid with the average ratings for the syllabus is 4,60; the average ratings for lesson plan is 4,62 and the average ratings for the student worksheet is 4,63. The student worksheet has also reached the practical qualification in mean percentage of student responses 94,61% in limited group trial with very practical criteria. Based on the results of this research can be concluded that the product in the form of syllabus, Lesson Plan and Student Worksheet mathematics with discovery learning model on subject Circle for grade XI is considered very valid and practical.Key Words: Research and Development, Mathematics Learning Instruments,Discovery Learning model, Circle